1994
DOI: 10.1002/macp.1994.021951001
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric surfactant systems in the asymmetric hydrogenation of amino acid precursors with a rhodium complex

Abstract: The synthesis of new types of soluble and insoluble amphiphilic systems is described, being polysoaps, crosslinked polysoaps, an amphiphilised ion exchanger, and ion exchangers loaded with ionic surfactants. It was possible to synthesise insoluble polymeric systems which nevertheless showed micellar properties. The polymers were tested as aids in the stereospecific hydrogenation of (2)-methyl a-acetamidocinnamate to the methyl ester of N-acetylphenylalanine ( R ) by means of an optically active rhodium complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…The activity and selectivity of the immobilized Rh catalyst was comparable with the homogeneous analog (Scheme 15.2 ). Flach et al reported another strategy of entrapping a Rh complex on the surface of immobilized surfactants through hydrophobic interactions ( Figure 15.3 ) [11] . No metal leaching was observed while repeating the hydrogenation experiment ten times in water.…”
Section: Noncovalent Binding Of Homogeneous Catalystsmentioning
confidence: 99%
“…The activity and selectivity of the immobilized Rh catalyst was comparable with the homogeneous analog (Scheme 15.2 ). Flach et al reported another strategy of entrapping a Rh complex on the surface of immobilized surfactants through hydrophobic interactions ( Figure 15.3 ) [11] . No metal leaching was observed while repeating the hydrogenation experiment ten times in water.…”
Section: Noncovalent Binding Of Homogeneous Catalystsmentioning
confidence: 99%
“…[16] Sodium 10-undecenylsulfate (7). Dry pyridine (60 mL) was cooled in an ice-bath for 15 min and chlorosulfonic acid (14 g, 0.12 mol) was added dropwise, followed by the addition of 10-undecen-1-ol (17 g, 0.1 mol) in 20 mL dichloromethane.…”
Section: Anionic Amphiphilesmentioning
confidence: 99%
“…The addition of both monomeric [17][18][19] and polymeric [19][20][21] surfactants significantly enhances the activity and the enantioselectivity. [22] The addition of micelleforming surfactants is necessary for this reaction, because an increase in the solubility of lipophilic substrates in water is required.…”
Section: Hydrogenationmentioning
confidence: 99%
“…The use of polymeric surfactants which form micelle-like structures could solve this problem. Regen [23] and Janout [24] have already utilized amphiphilic polymers in phase-transfer catalysis, and Flach et al [20,21] have synthesized new types of soluble and insoluble polysoaps for the use in asymmetric hydrogenation.…”
Section: Hydrogenationmentioning
confidence: 99%
See 1 more Smart Citation